STUDENTS’ VOCABULARY MASTERY TOWARD WATCHING ENGLISH FILM - Ayu Melati Ningsih; Vera Kristiana (PROJECT (Professional Journal of English Education), 2022)
The study deals with improving students’ vocabulary mastery through watching English films. The formulations of the problem are (1)Is watching English films effective in increasing students’ vocabulary? (2) What  English film can improve students’ vocabulary?. The purpose of the study is (1) to find out the effectiveness of watching English film can increase students’ vocabulary. (2) to know kind of English film can improve students’ vocabulary. The sample of this research is forty students from the second  yearsstudents of SMA Ksatria Medan. The technique of the collecting of the data by using questionare and test. The result from the research is students can improve vocabularie toward watching English films. Keywords:  Watching, English Film,Vocabulary Mastery